Identifying Key Factors of Rail Transit Service Quality: An Empirical Analysis for Istanbul - Isikli, Erkan; Aydin, Nezir; Celik, Erkan; Gumus, Alev Taskin (ELSEVIER, 2017)
Providing a high quality of service in public transportation is essential to reduce dissatisfactions stemming from traffic congestion and noise. Public transport providers need to find ways to dilute the effects of immoderate use of private cars in big cities while maintaining a sufficient level of customer satisfaction. This study aimed to identify the key service quality (SQ) factors that drive passenger satisfaction in Istanbul's rail transit (RT) system using data obtained from an extensive survey conducted by the Istanbul Public Transportation Co. A total of 11,116 passengers who used rail transport from May 15-June 3, 2012, and June 17-July 3, 2013, were interviewed in person. The relative importance of the SQ factors was assessed so that service provision could be prioritized and the enhancement of passenger satisfaction can be achieved employing several social choice techniques. The results indicate that, from an overall perspective, waiting time, crowdedness in cars, and fare are the SQ factors that best reflect the public good.
Keywords: Service quality; public transportation; rail transit systems; stated preferences; fallback voting; Istanbul; IMPROVE CUSTOMER SATISFACTION; PUBLIC TRANSPORT; PASSENGERS; FRAMEWORK; NETWORK; SYSTEMS; ACCESS; IMPACT; Transportation